2003
DOI: 10.1086/375033
|View full text |Cite
|
Sign up to set email alerts
|

Average Risks of Breast and Ovarian Cancer Associated with BRCA1 or BRCA2 Mutations Detected in Case Series Unselected for Family History: A Combined Analysis of 22 Studies

Abstract: Germline mutations in BRCA1 and BRCA2 confer high risks of breast and ovarian cancer, but the average magnitude of these risks is uncertain and may depend on the context. Estimates based on multiple-case families may be enriched for mutations of higher risk and/or other familial risk factors, whereas risk estimates from studies based on cases unselected for family history have been imprecise. We pooled pedigree data from 22 studies involving 8,139 index case patients unselected for family history with female (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
2,192
10
84

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,184 publications
(2,383 citation statements)
references
References 36 publications
60
2,192
10
84
Order By: Relevance
“…Figure 1 shows the cumulative incidence of breast cancer to age 50 years in smokers and non-smokers, based on our estimated relative risk associated with smoking, and the pooled estimates of cumulative risk from Antoniou et al [19]. For BRCA1 carriers, we predict that 60% of smokers will develop breast cancer by age 50 years, compared to about 35% of nonsmokers.…”
Section: Smoking and Breast Cancer Riskmentioning
confidence: 92%
“…Figure 1 shows the cumulative incidence of breast cancer to age 50 years in smokers and non-smokers, based on our estimated relative risk associated with smoking, and the pooled estimates of cumulative risk from Antoniou et al [19]. For BRCA1 carriers, we predict that 60% of smokers will develop breast cancer by age 50 years, compared to about 35% of nonsmokers.…”
Section: Smoking and Breast Cancer Riskmentioning
confidence: 92%
“…Other methods are used which depend on the reporting of cancers by family members. The lifetime risk of breast cancer in women who carry a deleterious BRCA1 or BRCA2 mutation is estimated to be as high as 80% -or roughly 10 times greater than that of the general population -but several estimates are lower (Ford et al, 1998;Risch et al, 2001;Antoniou et al, 2003;King et al, 2003). In a cohort of 76 BRCA1 mutation carriers from Rotterdam, eight invasive cancers were detected during 318 person-years of follow-up (Meijers-Heijboer et al, 2001) -an annual incidence of 2.5%.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies indicate that a mutation in a mismatch repair gene is found in approximately 40% to 80% of families that meet the Amsterdam I criteria and only about 5% to 50% of families meeting the Amsterdam II criteria. 15 Similarly, only about 5% to 10%of unselected patients with breast cancer 16 and 20% to 25% of patients with hereditary breast cancer 17 are found to carry a deleterious BRCA1 or BRCA2 mutation. Additionally, a number of other genes associated either with rare high-penetrance syndromes or a more moderate penetrance were identified.…”
Section: Single/limited Gene Testingmentioning
confidence: 99%